Maternal representations in the dreams of pregnant women: a prospective comparative study - Lara-Carrasco, Jessica; Simard, Valérie; Saint-Onge, Kadia; Lamoureux-Tremblay, Vickie; Nielsen, Tore (Frontiers in Psychology, 2013)
Dreams are thought to respond to self- and socially-relevant situations that evoke strong emotions and require rapid adaptation. First pregnancy is such a situation during which maternal mental representations (MMR) of the unborn baby, the self and significant others undergo remodelling. Some studies suggest that dreams during pregnancy contain more MMR and are more dysphoric, but such studies contain important methodological flaws. We assessed whether dreamed MMR, like waking MMR, change from 7 months to birth, and whether pregnancy–related themes and non-pregnancy characteristics are also transformed. Sixty non-pregnant and 59 pregnant women (37 early and 22 late 3rd trimester) completed demographic and psychological questionnaires and 14-day home dream logs. Dream reports were blindly rated and later analyzed following four dream categories: 1) Dreamed MMR, 2) Quality of baby/child representations, 3) Pregnancy-related themes, 4) Non-pregnancy characteristics. Controlling for age, relationship and employment status, education level and state anxiety, pregnant groups reported more dreams depicting themselves as a mother or with babies/children than did non-pregnant women (all p≤0.006). Baby/child representations were less specific in late 3rd than in early 3rd trimester (p=0.005) and than in non-pregnant women (p=0.01). Pregnant groups also had more pregnancy, childbirth and fetus themes (all p≤.01). Childbirth content was higher in late than in early 3rd trimester (p=0.01). Pregnant groups had more morbid elements than did the non-pregnant group (all p<.05). Dreaming during pregnancy appears to reflect daytime processes of remodelling MMR of the woman as a mother and of the unborn baby, and parallels a decline in the quality of baby/child representations in the last stage of pregnancy. More frequent morbid content in late pregnancy suggests that the psychological challenges of pregnancy are reflected in a generally more dysphoric emotional tone in dream content.